2009
DOI: 10.2478/s11534-009-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure factors of binary liquid metal alloys within the square-well model

Abstract: Abstract:The procedure suggested previously for the description of the square-well (SW) fluid within the framework of the mean spherical approximation is applied to calculate the structure factors of pure Na, pure K, and 0.5Na-0.5K alloy in liquid state. It is shown that our variations of the SW depth and SW width enable us to achieve a good agreement between calculated and experimental structure factors. The procedure under consideration gives more accurate results than the random phase approximation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Two-length-scale potentials like we study are widely used 31,32,33,34,35,36,37,38,39,40,40 ; they qualitatively describe effective interactions in molecular systems, 41,42 soft matter systems 43,44,45,46,47 and metallic alloys 14,48,49,50,51 where QC formation has been experimentally observed but not completely accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Two-length-scale potentials like we study are widely used 31,32,33,34,35,36,37,38,39,40,40 ; they qualitatively describe effective interactions in molecular systems, 41,42 soft matter systems 43,44,45,46,47 and metallic alloys 14,48,49,50,51 where QC formation has been experimentally observed but not completely accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier paper [16] has shown that the peak of the pair distribution function increases with the increase in the hard-sphere radius. And the recent article [31] has shown that the peak value of the liquid structure factor increases with the increase of width and depth of the square well part of the potential. Hence, we need to choose the values of the parameter carefully in order to obtain a good quantitative agreement between the theoretically obtained pair distribution function values and the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…We used fixed values for the parameters a, b, V 0 throughout our calculation. Some of the earlier papers (classical calculations) [16,31] have discussed the effect of varying the parameters to both the pair distribution function and the liquid structure factor. The earlier paper [16] has shown that the peak of the pair distribution function increases with the increase in the hard-sphere radius.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, theoretical approaches serve as an efficient instrument for investigations in this area. One of them is the square-well (SW) model, which is actively applied to liquid metals and their alloys [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%